Employing Circular Economy Approach for Construction & Demolition (C&D) Waste Management in Application of Industrialised Building System (IBS) - Eizzad Amirul Arash Mohd Nizam; Yunus, Riduan; Syed Burhanuddin Syed Mohamad; Pratiwi Setyaning Putri; Ezhwan Nur Arshad (International Journal of Sustainable Construction Engineering and Technology, 2026)
The construction industry is increasingly adopting the Circular Economy (CE) to promote sustainability. Industrialised Building Systems (IBS), which involve the off-site manufacturing of building components, are recognised as a key method for advancing CE goals due to their potential for waste reduction and efficient resource use. In Malaysia, the adoption of IBS has been limited. This is primarily due to significant knowledge gaps among stakeholders, including a lack of understanding, inadequate education, and the perceived complexity of integrating IBS with circular economy practices. This research aims to bridge this gap by developing a robust framework to evaluate circular economy performance criteria specifically for Industrialised Building Systems. The study conducts a rigorous analysis of existing evaluation tools, such as lifecycle cost analysis (LCA) and material reuse indicators. It organises and categorises these resources to create a practical framework that addresses the root causes of stakeholder resistance. The research confirms the significant potential of IBS to drive CE objectives, from waste minimisation to lifecycle sustainability. However, it also highlights the critical need for refined evaluation tools and enhance stakeholder education to fully realise these benefits. The proposed framework provides actionable insights for policymakers and industry practitioners to seamlessly integrate CE principles into all phases of IBS projects. By adopting this structured approach, the construction industry can transform IBS into a cornerstone of sustainable practice, setting a new benchmark for CE-driven innovation in Malaysia.